2007
DOI: 10.1002/jbm.a.31623
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of titanium into calcium silicate improved their chemical stability and biological properties

Abstract: Calcium silicate (CaSiO(3)) is regarded as a potential bioactive material. However, its poor chemical stability and cytocompatibility limits its biological applications. The aim of this study is to incorporate Titanium (Ti) into CaSiO(3) to produce a ceramic with improved chemical stability and biological properties. Sphene (CaTiSiO(5)) ceramics were prepared by sintering sol-gel-derived CaTiSiO(5) powder compacts and their chemical stability was assessed by measuring the ions released and weight loss after so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 32 publications
(50 reference statements)
2
74
0
Order By: Relevance
“…Compared with HT coatings, less Si and Ca ions were released from SP coatings, which was possibly the reason for the failure of Ca and P compound precipitation on SP coatings. Although HT coatings have high ability to release Ca and Si ions compared with SP coatings, the released amount is far less than that from CaO -SiO 2 materials [22,23,27,49,50]. In addition, the stability of HT coatings can be contributed by two factors: firstly, the slower release of Si compared with Ca ions can maintain the SiO 2 networks for a longer time; secondly, the faster precipitation of Ca and P compounds can compensate for the release of Ca ions and may hinder further release of Ca and Si.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with HT coatings, less Si and Ca ions were released from SP coatings, which was possibly the reason for the failure of Ca and P compound precipitation on SP coatings. Although HT coatings have high ability to release Ca and Si ions compared with SP coatings, the released amount is far less than that from CaO -SiO 2 materials [22,23,27,49,50]. In addition, the stability of HT coatings can be contributed by two factors: firstly, the slower release of Si compared with Ca ions can maintain the SiO 2 networks for a longer time; secondly, the faster precipitation of Ca and P compounds can compensate for the release of Ca ions and may hinder further release of Ca and Si.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, designing CaO-SiO 2 -based coatings with a limited release of Ca and Si ions, which will not compromise the long-term stability of the coatings, would result in coatings with enhanced bioactivity. In our previous work, we reported that hardystonite (HT) or sphene (SP) ceramics, produced by the addition of ZnO [22] or TiO 2 [23], respectively, into the CaO -SiO 2 for SP [25]) are closer to that of Ti-6Al-4V alloys, implying that higher bonding strength should be obtained. Therefore, it is plausible to suggest that HT and SP would be suitable candidate coatings for orthopaedic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the plasma spraying technique produced sphene coating with denser microstructure than the sol-gel technique. We recently demonstrated that sol-gel sphene coating possesses excellent chemical stability and enhanced bonding strength compared with sol-gel HAp-coated Ti-6Al-4V (Wu et al 2008a(Wu et al -c , 2008. However, the sol-gel sphene coatings can only be sintered at relatively low temperature (less than 9008C) as higher temperature (more than 9008C) sintering will oxidize and damage the surface of the metal.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial activity of the HOB cultured on coating and Ti-6Al-4V discs was determined by colorimetric assay, which detected the conversion of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTS; Promega, Madison, WI, USA) to formazan, as detailed previously (Wu et al 2008a(Wu et al -c , 2008. Cells were harvested with 0.1 per cent trypsin-EDTA solution in PBS and resuspended in full culture medium as detailed above.…”
Section: Proliferation Of Hobmentioning
confidence: 99%
“…Generally, the ionic environment and material surface are two main factors which influence the interaction of cells and biomaterials [7,[26][27][28][29]. In this study, silk modification did not create any significant effect on either ionic release or weight loss of MBG scaffolds.…”
Section: Physio-chemistry and Biological Property Of Silk-modified Mbmentioning
confidence: 50%